2022
DOI: 10.3390/ijms23168943
|View full text |Cite
|
Sign up to set email alerts
|

Iron Source and Medium pH Affect Nutrient Uptake and Pigment Content in Petunia hybrida ‘Madness Red’ Cultured In Vitro

Abstract: Deficiency or excess of iron (Fe) and improper medium pH will inhibit the growth and development of plants, reduce the transfer and utilization of energy from the root to the leaf, and affect the utilization efficiency of inorganic nutrients. The most common symptom of Fe deficiency in plants is chlorosis of the young leaves. In this study, the effects of the iron source, in combination with the medium pH, on plant growth and development, plant pigment synthesis, and nutrient uptake in a model plant Petunia hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 111 publications
0
4
0
Order By: Relevance
“…The hydrogen ion (pH) concentration of the medium, in addition to the type and concentration of phytohormones, is another determinant of successful plant micropropagation [ 62 ]. The pH of the culture medium affects the availability and uptake of nutrients and therefore has a direct effect on plant development and growth [ 78 , 79 , 80 , 81 , 82 , 83 ]. To access the effect of medium pH on grapevine shoot proliferation, we compared the same medium formulation within two pH ranges, i.e., medium no.…”
Section: Resultsmentioning
confidence: 99%
“…The hydrogen ion (pH) concentration of the medium, in addition to the type and concentration of phytohormones, is another determinant of successful plant micropropagation [ 62 ]. The pH of the culture medium affects the availability and uptake of nutrients and therefore has a direct effect on plant development and growth [ 78 , 79 , 80 , 81 , 82 , 83 ]. To access the effect of medium pH on grapevine shoot proliferation, we compared the same medium formulation within two pH ranges, i.e., medium no.…”
Section: Resultsmentioning
confidence: 99%
“…Iron (Fe) is considered a key micronutrient in plants, as its active form is involved in many biological processes, such as chlorophyll synthesis, photosynthesis, respiration, oxidative stress responses, and nitrogen (N) assimilation [ 1 , 2 ]. In the earth’s crust, Fe is the fourth most abundant element, mostly present in the soil solution in ferric (Fe 3+ ) form, while only the ferrous form (Fe 2+ ) can be used by non-graminaceous plants [ 3 ]. The low solubility of this micronutrient in soil solution limits its uptake by plants, particularly in alkaline and calcareous soils as they are characterized by high pH values [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Iron is essential for electron flow through the PSII-Cytb6f-PSI complex (Hantzis et al, 2018). When plants are Fe-deficient, photosynthesis is affected, chlorophyll cannot be produced normally; typical Fe-deficiency symptoms appeared (yellowing of young leaves), then plant growth decreased (Barhoumi et al, 2021;Krouma et al, 2008;Krouma et al, 2023;Guo et al, 2022). Other authors have shown that Fe deficiency is identified as the major reason of crop yield hampering in different plant species (Connorton et al, 2017;Pal et al, 2019;Merry et al, 2022;Dhaliwal et al, 2022).…”
Section: Introductionmentioning
confidence: 99%